(N~ETWERTI^NAQ TEKTONIKA ZONY SO^LENENIQ sREDINNOGO I `VNOGO tQNX(B-(N{ANQ (B/s - (NdVAMALOW(B, (NdVAWLON bAHODYROWI^s; (NzIQHANOW(B, (NzOHIDs; (NsIRADVITDINOW(B, (NwALI bURHANOWI^s ((NtA[KENT (B:s (NfAN(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 182-192s
Keywords: (NtEKTONIKA (B- (NtQNX(B-(N{ANXs; (N~ETWERTI^NYE OTLOVENIQs